Observation Assignment for Recreation and Sport Studies - Mason, Fred (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Description: RSS 2023 is an introductory level course in the sociology of sport and physical activity. The class generally averages about 150 students, and the majority of students taking this course are enrolled in the Bachelor of Science in Kinesiology program at the University of New Brunswick. For many, this will be among the very few, or even the only class they will take that offers a socio-cultural perspective of any sort. As such, the main goal of the class is to enable students to develop some inkling of a sociological imagination, with sport and physical activity as the topics under discussion. This out-of class paper assignment is designed to give students an opportunity to practically apply knowledge developed in the course, and to use a critical sociological perspective to analyze a real-world event. Students attend and make observations about a sporting event or some sort of organized physical activity in which they have interest. University varsity sports are popular due to ease of access, but the level of activities observed have ranged from top level professional sports events, to university and high school intramurals, to micro level (under 4 years of age) soccer. Tailoring to their own interests, some students have also observed charity fun runs, aqua-size classes and creative dance shows. Students focus their observations on, and ultimately write a 5-6 page paper about major social issues apparent at the activity/event. Initially, students could choose from among a range of course topics and themes to write about, which produced some creative and critical writing among the best students. Many others struggled however, over deciding what sort of social issues to even begin with. Thus, the assignment has been modified over time to concentrate on four major course topics/issues: gender, race, social class and commercialization. This enables all students to focus on relevant social concerns and apply course materials, while still allowing more advanced critical observation from students who are more sociologically inclined.